International Retrospective Chart Review of Treatment Patterns in Severe Familial Mediterranean Fever, Tumor Necrosis Factor Receptor–Associated Periodic Syndrome, and Mevalonate Kinase Deficiency/Hyperimmunoglobulinemia D Syndrome. Issue 4 (3rd March 2017) - Ozen, Seza; Kuemmerle‐Deschner, Jasmin B.; Cimaz, Rolando; Livneh, Avi; Quartier, Pierre; Kone‐Paut, Isabelle; Zeft, Andrew; Spalding, Steve; Gul, Ahmet; Hentgen, Veronique; Savic, Sinisa; Foeldvari, Ivan; et al.
Abstract : Objective: Periodic fever syndrome (PFS) conditions are characterized by recurrent attacks of fever and localized inflammation. This study examined the diagnostic pathway and treatments at tertiary centers for familial Mediterranean fever (FMF), tumor necrosis factor receptor–associated periodic syndrome (TRAPS), and mevalonate kinase deficiency (MKD)/hyperimmunoglobulinemia D syndrome (HIDS). Methods: PFS specialists at medical centers in the US, the European Union, and the eastern Mediterranean participated in a retrospective chart review, providing de‐identified data in an electronic case report form. Patients were treated between 2008 and 2012, with at least 1 year of followup; all had clinical and/or genetically proven disease and were on/eligible for biologic treatment. Results: A total of 134 patients were analyzed: FMF (n = 49), TRAPS (n = 47), and MKD/HIDS (n = 38). Fever was commonly reported as severe across all indications. Other frequently reported severe symptoms were serositis for FMF patients and elevated acute‐phase reactants and gastrointestinal upset for TRAPS and MKD/HIDS. A long delay from disease onset to diagnosis was seen within TRAPS and MKD/HIDS (5.8 and 7.1 years, respectively) compared to a 1.8‐year delay in FMF patients. An equal proportion of TRAPS patients first received anti–interleukin‐1 (anti‐IL‐1) and anti–tumor necrosis factor (anti‐TNF) biologic agents, whereas IL‐1 blockade was the main choice for FMF patients resistant to colchicine and MKD/HIDS patients. For TRAPS patients, treatment with anakinra versus anti‐TNF treatments as first biologic agent resulted in significantly higher clinical and biochemical responses ( P  = 0.03 and P  < 0.01, respectively). No significant differences in responses were observed between biologic agents among other cohorts. Conclusion: Referral patterns and diagnostic delays highlight the need for greater awareness and improved diagnostics for PFS. This real‐world treatment assessment supports the need for further refinement of treatment practices.